2013
DOI: 10.1016/j.alcohol.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Stress–response pathways are altered in the hippocampus of chronic alcoholics

Abstract: The chronic high-level alcohol consumption seen in alcoholism leads to dramatic effects on the hippocampus, including decreased white matter, loss of oligodendrocytes and other glial cells, and inhibition of neurogenesis. Examining gene expression in post mortem hippocampal tissue from 20 alcoholics and 19 controls allowed us to detect differentially expressed genes that may play a role in the risk for alcoholism or whose expression is modified by chronic consumption of alcohol. We identified 639 named genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 95 publications
(140 reference statements)
6
111
0
Order By: Relevance
“…The LC is profoundly impacted by stress and its dysregulation can increase the risks of both ethanol dependence and the potential for relapse (Morilak et al 2005). Intra-gastric delivery of ethanol to non-handled, freely moving rats increases LC neuronal activity, as measured by accumulation of c-Fos, a marker of recent neuronal activation, supporting the notion that acute ethanol induces activation of LC neurons (Kolodziejska-Akiyama et al 2005; McClintick et al 2013; Lee et al 2011). Additionally, administration of ethanol intracerebroventricularly normally stimulates adrenocorticotropin (ACTH) release from the PVN; however, when the LC was lesioned, release was potentiated (Selvage 2012), indicating a direct role for the LC in ethanol induced HPA axis activation.…”
Section: Introductionsupporting
confidence: 53%
“…The LC is profoundly impacted by stress and its dysregulation can increase the risks of both ethanol dependence and the potential for relapse (Morilak et al 2005). Intra-gastric delivery of ethanol to non-handled, freely moving rats increases LC neuronal activity, as measured by accumulation of c-Fos, a marker of recent neuronal activation, supporting the notion that acute ethanol induces activation of LC neurons (Kolodziejska-Akiyama et al 2005; McClintick et al 2013; Lee et al 2011). Additionally, administration of ethanol intracerebroventricularly normally stimulates adrenocorticotropin (ACTH) release from the PVN; however, when the LC was lesioned, release was potentiated (Selvage 2012), indicating a direct role for the LC in ethanol induced HPA axis activation.…”
Section: Introductionsupporting
confidence: 53%
“…Notably, bioinformatic analysis to identify cell-type-specific gene expression indicates involvement of astrocytes in females during intoxication. Evidence of glial activation and some aspects of neuroinflammation have been observed in postmortem brain tissue from alcoholics (Zou and Crews, 2012, Crews et al, 2013, McClintick et al, 2013). Chronic alcohol exposure can result in immune dysfunction and immunosuppression, at least in some tissues (Kaphalia and Calhoun, 2013, Khocht et al, 2013, Mehta et al, 2013, Parlet et al, 2014), and alcoholics frequently develop severe respiratory infections which result in increased hospital stays and a higher likelihood of intensive care unit admission (Saitz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genotype-specific FKBP5 DNA methylation may mediate these genechildhood trauma interactions (Klengel et al, 2013). More importantly, a recent study has reported differential expression of the FKBP5 gene in postmortem brains of alcoholics (McClintick et al, 2013), suggesting a role for this gene in the pathophysiology of AD. Here, we examined whether genetic variation at the FKBP5 locus moderates the severity of alcohol withdrawal in alcohol-dependent patients who had consumed their last drink within 48 h of admission to an inpatient unit.…”
Section: Introductionmentioning
confidence: 99%